1998
DOI: 10.1042/bj3300777
|View full text |Cite
|
Sign up to set email alerts
|

A dehydrogenase-mediated recycling system of NADPH in plant peroxisomes

Abstract: The presence of the two NADP-dependent dehydrogenases of the pentose phosphate pathway has been investigated in plant peroxisomes from pea (Pisum sativum L.) leaves. Both enzymes, glucose-6-phosphate dehydrogenase (G6PDH; EC 1.1.1.49) and 6-phosphogluconate dehydrogenase (6PGDH; EC 1.1.1.44), were present in the matrix of leaf peroxisomes, and their kinetic properties were studied. G6PDH and 6PGDH showed a typical Michaelis-Menten kinetic saturation curve, and had specific activities of 12.4 and 29.6 mU/mg pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 61 publications
(84 reference statements)
6
115
0
Order By: Relevance
“…It is worth noting that some of the cofactors involved in the L-Arg-dependent NOS activity in plant peroxisomes have been described in previous studies (Corpas et al, 2009b). Several NADP-dehydrogenases can produce NADPH (Corpas et al, 1998, while the presence of calmodulin in plant peroxisomes has been also demonstrated (Yang and Poovaiah, 2002) being both essential elements for this activity. These results could be important, particularly given that inducible NOS has also been reported in peroxisomes of rat hepatocytes (Stolz et al, 2002;Loughran et al, 2005).…”
Section: Pex12 and Pex13 Appear To Be Involved In The Peroxisomal Impmentioning
confidence: 99%
“…It is worth noting that some of the cofactors involved in the L-Arg-dependent NOS activity in plant peroxisomes have been described in previous studies (Corpas et al, 2009b). Several NADP-dehydrogenases can produce NADPH (Corpas et al, 1998, while the presence of calmodulin in plant peroxisomes has been also demonstrated (Yang and Poovaiah, 2002) being both essential elements for this activity. These results could be important, particularly given that inducible NOS has also been reported in peroxisomes of rat hepatocytes (Stolz et al, 2002;Loughran et al, 2005).…”
Section: Pex12 and Pex13 Appear To Be Involved In The Peroxisomal Impmentioning
confidence: 99%
“…The C-terminal 10-amino acid residues of 6PGDH, however, directed EYFP to punctate subcellular structures that moved along cytoplasmic strands and coincided with peroxisomes ( Figures 4N1 and 4N2). Although not identified within the proteome analysis, subcellular targeting of 6P-gluconolactonase (6PGL), the precedent enzyme of 6PGDH in the peroxisomal OPPP (Corpas et al, 1998(Corpas et al, , 1999, was also investigated using one specific isoform (At5g24400) out of five Arabidopsis homologs. This enzyme carries both a predicted N-terminal transit peptide and a conserved PTS1 (SKL>; Reumann et al, 2004).…”
Section: Experimental Verification Of Predicted Ptssmentioning
confidence: 99%
“…A characteristic property of these oxidative organelles is their metabolic plasticity since their enzymatic content can vary depending on the organism, cell/ tissue-type, and environmental conditions (13,14). In higher plants, peroxisomes contain a complex battery of antioxidative enzymes such as catalase, superoxide dismutase (15,16), the components of the ascorbate-glutathione cycle (17), and the NADP-dehydrogenases of the pentose-phosphate pathway (18). Likewise, the generation of superoxide radicals has also been reported in the matrices and membranes of peroxisomes (19 -21).…”
Section: Nitric Oxide (No)mentioning
confidence: 99%